The astrobiological landscape : philosophical foundations of the study of cosmic life - Ćirković, Milan M. (Cambridge astrobiology, 2012)
Astrobiology is an expanding, interdisciplinary field investigating the origin, evolution and future of life in the universe. Tackling many of the foundational debates of the subject, from discussions of cosmological evolution to detailed reviews of common concepts such as the 'Rare Earth' hypothesis, this volume is the first systematic survey of the philosophical aspects and conundrums in the study of cosmic life. The author's exploration of the increasing number of cross-over problems highlights the relationship between astrobiology and cosmology and presents some of the challenges of multidisciplinary study. Modern physical theories dealing with the multiverse add a further dimension to the debate. With a selection of beautifully presented illustrations and a strong emphasis on constructing a unified methodology across disciplines, this book will appeal to graduate students and specialists who seek to rectify the fragmented nature of current astrobiological endeavour, as well as curious astrophysicists, biologists and SETI enthusiasts.